2013
DOI: 10.3389/fphar.2013.00117
|View full text |Cite
|
Sign up to set email alerts
|

Acute nicotine administration effects on fractional anisotropy of cerebral white matter and associated attention performance

Abstract: Introduction: Nicotinic acetylcholine receptors are present in the cerebral white matter (WM). We hypothesized that WM response to nicotine can be detected by diffusion tensor imaging (DTI); and that such responses may be associated with nicotine-led cognitive enhancement in sustained attention.Methods: A randomized, nicotine-placebo patch, crossover, double-blind clinical trial in two non-overlapping cohorts of smokers was used to test the hypothesis. The discovery cohort consisted of 39 subjects (N = 20/19 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 64 publications
(92 reference statements)
0
28
0
Order By: Relevance
“…As discussed above, recent data from adult studies suggest effects of acute nicotine (Kochunov et al, 2013) – and of time since last cigarette (Savjani et al, 2014) – on DTI indices. Thus, an important consideration for future studies will be how best to disentangle acute versus chronic effects of nicotine in adolescents and young adults.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…As discussed above, recent data from adult studies suggest effects of acute nicotine (Kochunov et al, 2013) – and of time since last cigarette (Savjani et al, 2014) – on DTI indices. Thus, an important consideration for future studies will be how best to disentangle acute versus chronic effects of nicotine in adolescents and young adults.…”
Section: Discussionmentioning
confidence: 94%
“…In human adult populations, increases in genual corpus callosal FA have been reported following acute nicotine administration (Kochunov et al, 2013). Thus, increased FA among adolescent/young adult smokers may be a consequence of exposure to nicotine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although smoking (number of cigarettes/d) did not significantly correlate with FA in patients or controls, these factors may still have influenced our findings. 57,58 Twenty-six per cent of the patients dropped out during follow-up, and those who dropped out had more years of education than those who did not drop out. As correction for education did not alter our results, we consider it unlikely that baseline differences substantially influenced our results.…”
Section: Limitationsmentioning
confidence: 99%
“…In both neuropathology and neuroimaging, it is uncertain whether white matter changes are an intrinsic component of schizophrenia or are the consequence of neuroleptic treatment, social deprivation, or other epiphenomena related to suffering from a chronic psychiatric disorder. A number of studies have suggested that the DTI abnormalities in schizophrenia are confounded by multiple factors, including the duration of illness and treatment with antipsychotic medications (Konopaske et al, 2006(Konopaske et al, , 2008, age (Kochunov et al, 2013a(Kochunov et al, , 2013bGiezendanner et al, 2013;Mandl et al, 2013), sex of the subjects (Savadjiev et al, 2014), and even heavy cigarette smoking (Cullen et al, 2012;Kochunov et al, 2013aKochunov et al, , 2013b.…”
Section: Pathological Changes Of White Matter In Schizophreniamentioning
confidence: 99%